Los sistemas de agricultura en el Istmo Centroamericano - Soria V, J. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2015)
The main agricultural systems in the Central American area for both local food consumption and export crops are monocultures, multiple cultures, associated cultures and their combinations. The efficiency of these systems different strata of producers, and on the ecological conditions of the tropics. The need for more ecologically oriented research, with special emphasis on the small farmer and his economic and social status, is clearly evident.